Budaya Longko’ Toraya Sebagai Etika Sosial Dalam Perspektif Iris Murdoch - Wandrio Salewa; Mariance Mariance (Melo: Jurnal Studi Agama-agama, 2022)
This paper tries to explore the longko 'Toraya culture as a social ethic in the life of the Toraja people. Today's longko' Toraya culture is sometimes misunderstood as a necessity that becomes a burden. Especially in the midst of a materialistic and individualistic life and an instant lifestyle. This study uses a qualitative approach with literature, ethnography and observation and is framed in the perspective of Iris Murdoch which will strengthen the longko' culture as social ethics. So the result of this research is to provide assistance to others as an act that goes out of reality towards a loving and fair concern in seeing the needs of others as a necessity. When this is not done it will cause feelings of shame.